Efficacy of placement of dual ureteral stents after laser incision and balloon dilation for ureteral stricture - 杉野 輝明; 濵本 周造; 海野 怜; 田口 和己; 安藤 亮介; 岡田 淳志; 安井 孝周 (Japanese Journal of Endourology, 2021)
In recent years, the indications for endoscopic treatment of ureteral stricture have expanded. We introduced a method of placement of dual ureteral stents after laser incision and balloon dilation for the treatment of ureteral stricture and investigated its usefulness. The subjects were 10 patients who underwent endoscopic surgery for ureteral stricture between January 2016 and March 2019. In all cases, balloon dilation was performed after laser incision. Double 4.7 Fr ureteral stents were placed and they were removed 4 to 8 weeks after the surgery. Improvement of hydronephrosis was observed in eight cases (80％). The median follow-up period was 251.5 days, and no restenosis was observed in any of the eight patients. The method of combining laser incision with balloon dilation and placement of dual ureteral stents after surgery was considered useful.